Physicochemical Properties of ACE Inhibitory Peptides from Jujube Kernel by Enzymatic Method - Liming TAN; Yan CAO; Haisheng PEI; Jianxiong HAO; Huiying LI (Shipin gongye ke-ji, 2022)
In this study, the defatted jujube kernel residue was extracted by alkali solubilization and acid seperation method to obtain jujube kernel protein, and the angiotensin converting enzyme (ACE) inhibitory peptide was obtained by enzymatic hydrolysis of neutral protease and alkaline protease. Taking jujube kernel as the research object, the physicochemical properties of ACE inhibitory peptide were studied. In this paper, the functional activity and nutritional value of ACE inhibitory peptide in defatted jujube kernel were demonstrated from the aspect of amino acids by analyzing the basic nutrients of defatted jujube kernel and the amino acid composition of ACE inhibitory peptide in enzymolyzed jujube kernel. The enzymatic hydrolysis effect of jujube kernel protein was proved by molecular weight distribution, particle size distribution and microscopic structure observation. Finally, the physical and chemical properties of jujube seed, including solubility, thermal stability, water and oil retention, foaming and foaming stability, emulsification and emulsification stability, and sensory characteristics before and after proteolysis, were compared and analyzed. It was found that the protein content of defatted jujube kernel was (73.40±0.23) g/100 g, and the protein content was higher. The essential amino acid content and hydrophobic amino acid content in ACE inhibitory peptide of jujube kernel were 36.48% and 51.14%, and the content of glutamate was the highest. The molecular weight of ACE inhibitory peptides in Zizyphus jujube kernel was mainly in the range of 1000~3000 Da, accounting for 97.50%, and the polydispersity index was 1.088, indicating a narrow molecular weight distribution. The protein structure of jujube kernel was broken before and after enzymolysis of ACE inhibitory peptides, and the enzymolysis was sufficient. The study of physical and chemical properties showed that compared with the protein before enzymolysis, the thermal stability, solubility, water holding capacity, oil holding capacity and emulsification stability of the ACE inhibitory peptide of jujube kernel were significantly improved, while the foaming, foaming stability and emulsification ability significantly decreased（P<0.05）. The results showed that the physicochemical properties of ACE inhibitory peptides in jujube kernel were significantly improved compared with those before enzymolysis（P<0.05）. The discovery of related physicochemical properties laid a research foundation for the follow-up research, and provided a theoretical basis for the production and application of ACE inhibitory peptides in jujube kernel.